Service Recovery Paradox In Indian Banking Industry: An Empirical Investigation - Garg, Arunesh (UI Scholars Hub, 2013)
The present study examines existence of service recovery paradox in Indian banking industry. The study is taken up in the tri-city of Chandigarh, Panchkula and Mohali. The respondents are categorized into failure and no-failure groups on the basis of their service experience. Failure group constitutes those respondents who have experienced service recovery, and has been further divided into five sub-groups ranging from service recovery++ (service recovery better than expected) to service recovery- - (service recovery worse than expected). Service recovery paradox is examined by comparing service recovery++ group with no-failure group. The study shows evidence for existence of service recovery paradox in relation to satisfaction. It has been concluded that for service recovery paradox to exist, recovery effort has to be exceptionally good and much better than expectation level of the customer. The study suggests that service managers should take service failure as an opportunity to appease customers by providing a much better than expected recovery experience. However, organizations should not plan to create service failure situations because if they falter on imparting the recovery, customer satisfaction may be influenced negatively.